Pengaruh Kompetensi, Integritas, dan Skeptisme Profesional Auditor terhadap Fraud Prevention dengan Kualitas Audit Sebagai Variabel Intervening: Studi pada BPKP Provinsi Sumatera Selatan - Nurhaliza Kurniasyari; Sopiyan AR; Ulfah Tika Saputri (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the influence of auditor competence, integrity, and professional skepticism on fraud prevention, with audit quality as an intervening variable among auditors at BPKP South Sumatera Province. The research employs a quantitative associative approach using purposive sampling technique. Data were collected through questionnaires and analyzed using the Partial Least Squares – Structural Equation Modeling (PLS-SEM) method with the assistance of SmartPLS version 4 software. The results indicate that auditor competence, integrity, and professional skepticism have a positive effect on fraud prevention. However, audit quality as a mediating variable between competence, integrity, and professional skepticism and fraud prevention does not have a significant effect.